'Fair and Equitable Treatment' in International Investment Law - Klager, Roland, 1982- (Cambridge : Cambridge University Press, 2011)
'A breach of fair and equitable treatment is alleged in almost every investor-state dispute. It has therefore become a controversial norm, which touches many questions at the heart of general international law. Roland Klager sheds light on these controversies by exploring the deeper doctrinal foundations of fair and equitable treatment and reviewing its contentious relationship with the international minimum standard. The norm is also discussed in light of the fragmentation of international law, theories of international justice and rational balancing, and the idea of constitutionalism in international law. In this vein, a shift in the way of addressing fair and equitable treatment is proposed by focusing on the process of justificatory reasoning'--
'Fair and Equitable Treatment in International Investment Law A breach of fair and equitable treatment is alleged in almost every investor-state dispute. It has therefore become a controversial norm, which touches many questions at the heart of general international law. Roland Klager sheds light on these controversies by exploring the deeper doctrinal foundations of fair and equitable treatment and reviewing its contentious relationship with the international minimum standard. The norm is also discussed in light of the fragmentation of international law, theories of international justice and rational balancing, and the idea of constitutionalism in international law. In this vein, a shift in the way of addressing fair and equitable treatment is proposed by focusing on the process of justificatory reasoning'--
Machine generated contents note: 1. Introduction; Part I. The Construction of Fair and Equitable Treatment: 2. Fundamentals for the construction of fair and equitable treatment; 3. Fair and equitable treatment and the international minimum standard; 4. The role of international law in the construction of fair and equitable treatment; Part II. The Concept of Fair and Equitable Treatment: 5. Conceptual challenges; 6. Fair and equitable treatment and justice; 7. Principles of fair and equitable treatment; Part III. The Position of Fair and Equitable Treatment in the International Legal System: 8. Fair and equitable treatment in the system of international law sources; 9. Fair and equitable treatment in the system of international investment law; 10. Summary.
Includes bibliographical references (pages 321-352) and index.
Keywords: Arbitration and award, International; Investments, Foreign (International law); Investments, Foreign -- Law and legislation